Cesium immobilization in perovskite-type Ba1-x(La, Cs)xZrO3 ceramics by sol-gel method. Issue 7 (May 2020) - Zhao, Jian; Li, Jie; Liu, Haifeng; Zhang, Xingquan; Zheng, Kui; Yu, Hongfu; Lian, Qihui; Wang, Hua; Zhu, Yongchang; Huo, Jichuan
Abstract: Radioactive and toxic cesium (Cs) is difficult to be immobilized due to the volatilizing at high temperatures. Ba1-x (La, Cs)x ZrO3 (x = 0, 0.1, 0.2, 0.3, 0.4) ceramics were synthesized by sol-gel method at a low temperature for Cs immobilization. The structural and morphological characterizations show that the Ba1-x (La, Cs)x ZrO3 ceramics composed of closely arranged particles have a single perovskite structure, and Cs has been successfully incorporated into the lattice. Leaching test shows that Cs has an excellent leaching rate (0.894 × 10 −3  g m −2  d −1 ) in Ba1-x (La, Cs)x ZrO3 ceramics, lower than the hollandite-rich synroc and pollucite. It reveals that the perovskite-type Ba1-x (La, Cs)x ZrO3 ceramics have high chemical stability and can be a potential alternative material to immobilize Cs.